(untitled) (Szociológiai Szemle, 2024)
The goal of this paper is to study the status attainment process in Hungary. Using data from four large-scale nation-wide representative surveys, we analyze the job histories of about 40,000 men between 1910 and 1991. We focuse on the effect of two main determinants of status attainment process: achievement and ascription, measured by respondent’s educational level and father’s occupation. Our main interest is to analyze how the influence of these two variables on status attainment varies over historical times and over the life course. The main hypothesis of the research is based on the industrialization theory assuming that the impact of achievement becomes larger and that of ascription becomes smaller over time. The other hypothesis is based on life-course theory assuming that both educational credentials and ascriptive features of social origin are replaced by other abilities and capitals collected and accumulated during the life course. We approach the research problem in two steps. First, we calculate descriptive statistics, change of average educational level, occupational attainment and social origin as well as the zero-order correlations between education and occupation just as between father’s occupation and respondent’s occupation for selected historical years by birth cohorts. Second, we estimate logistic regression models on status gains and status losses during the career and analyze the unconditioned effect of time and age, that of education and father’s occupation, as well as the changes of the impact of achievement and ascription over time and age. The analysis on career transitions in upward and downward direction is based on using a discrete time event history model on a person-period file. Both descriptive statistics and estimates from causal models on upward and downward mobility confirm the hypothesis on age effect. As expected, the influence of education and that of father’s occupation declines over age and as getting older these determinants tend to play a smaller role in the status attainment process. Our results basically confirm the industrialization hypothesis, too. We found the increasing trend for achievement and the decreasing trend for ascription, however, for both trends we found a reversal, both trends started to turn back to some extent after the mid-1980s.